2018
DOI: 10.3390/rs10101641
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating RADARSAT-2 for the Monitoring of Lake Ice Phenology Events in Mid-Latitudes

Abstract: Lake ice is an important component in understanding the local climate as changes in temperature have an impact on the timing of key ice phenology events. In recent years, there has been a decline in the in-situ monitoring of lake ice events in Canada and microwave remote sensing imagery from synthetic aperture radar (SAR) is more widely used due to the high spatial resolution and response of backscatter to the freezing and melting of the ice surface. RADARSAT-2 imagery was used to develop a threshold-based met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 43 publications
(73 reference statements)
3
24
1
Order By: Relevance
“…Ice cover typically forms between mid-December to early January and the process of melt begins between the middle of March and the beginning of April. Full ice cover typically lasts until the end of April but can persist until early May [22,27].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ice cover typically forms between mid-December to early January and the process of melt begins between the middle of March and the beginning of April. Full ice cover typically lasts until the end of April but can persist until early May [22,27].…”
Section: Methodsmentioning
confidence: 99%
“…Similar to ice estimates from temperature, remote sensing techniques to estimate freshwater lake ice thickness have seen limited application in mid-latitudes. Therefore, it is unclear whether or not these methods will see similar success for lake ice in these regions where ice conditions differ from the northern latitudes [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…They put forward a threshold-based classification methodology and observed that the HH and HV backscatter from the lake ice have significant temporal variability and interlake diversity. Murfitt et al (2018) used the RADARSAT-2 imagery to develop a threshold-based method to determine lake phenology events for the mid-latitude lakes in Central Ontario from 2008 to 2017. Wang et al (2018) also used RADARSAT-2 imagery (dual polarised) for developing a lake ice classification system acquired over lake Erie, with the IRGS method.…”
Section: Related Workmentioning
confidence: 99%
“…Their analysis showed that the algorithm could provide reliable discrimination between ice and open water with high overall classification accuracy (90.4%) when compared to Great Lakes image analysis charts from the Canadian Ice Service. Murfitt et al [87] developed a threshold-based approach for estimating ice phenology events for mid-latitude lakes in Central Ontario by tracking the temporal evolution in backscatter from HH-polarization RADARSAT-2 imagery (2008-2017). The authors reported mean absolute errors of 2.5-10 days for freeze events and 1.5-7.1 days for water clear-of-ice when compared to MODIS imagery.…”
Section: Lake Ice Covermentioning
confidence: 99%